From theory to practice: pilot plan to incorporate environmental knowledge in an education center. - López Alfaro, Nelly (2016)
This article collects the lessons learned from a pilot plan of an environmental education in a semi-private educational center. The working strategy about the environmental matter tried to approach different areas of action, e.g., administrative and academic field, as well as the community projection. Therefore, from kindergarten to high school levels, training courses were developed under a methodological strategy covering all the school stages. At the same time, the institutional policy, its administrative work, along with the involvement of the parents committee and their community projection were permeated.